Analisa Disiplin, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Negeri Sipil Bekangdam I/Bukit Barisan - Oktavianus Tarigan, Philip; Robain, Wilchan; Azwar Hasibuan, Hasrul (Journal of Comprehensive Science, 2025)
Organizations play an important role in achieving goals by managing production factors, one of which is human resources (HR). Work discipline, work motivation, and work environment are factors that influence employee performance in an organization. This study aims to analyze the influence of discipline, work motivation, and work environment on employee performance at the Bekangdam I/Bukit Barisan work unit. The novelty of this research lies in the integration of these three factors in the context of education and training in the Ministry of Defense of Indonesia. This research uses a quantitative approach with a causal associative research design, where these variables are tested for their impact on employee performance through regression analysis. Data were collected using questionnaires with Likert scales involving 25 civil servants (PNS) at Bekangdam I/Bukit Barisan. The results of the study indicate that work motivation has a positive and significant effect on employee performance, while work discipline and work environment have no significant effect. Simultaneously, these three factors do not have a significant impact on employee performance. This study concludes that to improve employee performance, the main focus should be placed on increasing work motivation, while discipline and work environment need to be further reviewed for improvement.